2011
DOI: 10.1371/journal.pone.0019103
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the Angiogenic Signal through the Activation of the TSC/mTOR/HIF Axis by the KSHV vGPCR in Kaposi's Sarcoma

Abstract: BackgroundKaposi's sarcoma (KS) is a vascular neoplasm characterized by the dysregulated expression of angiogenic and inflammatory cytokines. The driving force of the KS lesion, the KSHV-infected spindle cell, secretes elevated levels of vascular endothelial growth factor (VEGF), essential for KS development. However, the origin of VEGF in this tumor remains unclear.Methodology/Principal FindingsHere we report that the KSHV G protein-coupled receptor (vGPCR) upregulates VEGF in KS through an intricate paracrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 44 publications
2
84
0
Order By: Relevance
“…Indeed, many HHV8 genes, including v-GPCR [18], ORF50 [4,5] and vIL-6 [21], have been recognized as important transforming factors inducing a potent neoangiogenic capability in infected endothelial cells. Moreover, HHV8 infection causes a reprogramming of cell transcription, inducing the expression of cellular factors with proangiogenic activity, including VEGF, MCP-1, ATF4, mTOR, and ANGPTL4 [4,5,12,16,21,22]. In line with this, previous observations by our group evidenced a relevant presence of HHV8 in cutaneous vascular proliferative lesions, especially in eruptive cherry angiomas (CAs), and suggested that immunosuppression could be a substratum for HHV8 to explicate its neoangiogenic potential at skin level [1,2].…”
Section: Introductionsupporting
confidence: 78%
“…Indeed, many HHV8 genes, including v-GPCR [18], ORF50 [4,5] and vIL-6 [21], have been recognized as important transforming factors inducing a potent neoangiogenic capability in infected endothelial cells. Moreover, HHV8 infection causes a reprogramming of cell transcription, inducing the expression of cellular factors with proangiogenic activity, including VEGF, MCP-1, ATF4, mTOR, and ANGPTL4 [4,5,12,16,21,22]. In line with this, previous observations by our group evidenced a relevant presence of HHV8 in cutaneous vascular proliferative lesions, especially in eruptive cherry angiomas (CAs), and suggested that immunosuppression could be a substratum for HHV8 to explicate its neoangiogenic potential at skin level [1,2].…”
Section: Introductionsupporting
confidence: 78%
“…Multiple KSHV-encoded viral proteins have been demonstrated to activate the Notch pathway (3,6,12,(16)(17)(18)(38)(39)(40). We reported previously that KSHV LANA stabilizes ICN and contributes to cell proliferation (30).…”
Section: Lana Was the Major Component That Upregulated Hey1 Expressiomentioning
confidence: 98%
“…Of interest, direct and paracrine AKT activation of the TSC2/mTOR pathway has been shown to be necessary and sufficient for vGPCR oncogenesis (37). Although the different downstream mechanisms by which vGPCR-mediated mTOR drives vGPCR sarcomagenesis are still unclear, one includes the dramatic amplification of VEGF secretion, through the activation by vGPCR cytokines of multiple kinases including AKT, ERK, p38 and IKKβ, all of which can ultimately converge in TSC/mTOR activation and hypoxia-inducible factor (HIF) upregulation in (neighboring) non-vGPCR expressing cells (38). Another novel pro-angiogenic and pro-tumorigenic factor highly upregulated through vGPCR direct and paracrine HIF activation is Angiopoietin-like 4, a novel factor recently found to be involved in tumor progression and tumor metastasis through the regulation of endothelial cell-cell junctions (39; 40).…”
Section: Kshv Gpcr (Vgpcr)mentioning
confidence: 99%